1999
DOI: 10.1093/ajcn/69.4.672
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin and riboflavin-derived cofactors in adolescent girls with anorexia nervosa

Abstract: Background: Thyroid hormones, riboflavin, riboflavin cofactors, and organic acids were assessed in girls with anorexia nervosa. Objective: The objective was to examine the effect of malnutrition and low thyroid hormone concentrations on erythrocyte and plasma riboflavin metabolism and their relation with urinary organic acid excretion. Design: Seventeen adolescent girls with anorexia nervosa [body mass index (BMI; in kg/m 2 ): 14.8 ± 2.2] and 17 age-matched, healthy girls (control subjects; BMI: 20.5 ± 2.2) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
(30 reference statements)
0
14
0
3
Order By: Relevance
“…En relación con los déficits de tiamina se han recogido complicaciones como el síndrome de Wernicke 61 . Con respecto a otros micronutrientes hay resultados dispares, que no permiten establecer pautas generales 62,63 .…”
Section: Uso De Suplementosunclassified
“…En relación con los déficits de tiamina se han recogido complicaciones como el síndrome de Wernicke 61 . Con respecto a otros micronutrientes hay resultados dispares, que no permiten establecer pautas generales 62,63 .…”
Section: Uso De Suplementosunclassified
“…Research on riboflavin in adolescent girls with anorexia has shown some evidence of deficiency, but it is unclear if this finding is a result of inadequate intake or ineffective metabolism resulting from low levels of thyroid hormone. 31,34 Oral contraceptives have been linked to low riboflavin levels. No recommendation is available beyond supplementation at the RDA for patients with generally poor nutrition.…”
Section: Riboflavinmentioning
confidence: 99%
“…Le corticoreleasing-factor (CRF, qui a des propriétés anorexigènes) est augmenté de même que la cortisolémie. La fonction thyroï-dienne est perturbée avec baisse de l'hormone active, la T3, qui constitue un élément de l'adaptation à la dénutrition [27,29]. L'IGF1 est abaissée alors que la sécrétion de GH est augmentée montrant un état de résistance à la GH.…”
Section: Mécanismes Et Particularités De La Dénutrition De L'anorexieunclassified
“…Le suivi de l'ostéocalcine sérique est un bon index de l'anabolisme osseux [42]. Parmi les vitamines, il n'y a pas de déficit en vitamines liposolubles en particulier en vitamine D. Seules les vitamines C et B1 [21,22] peuvent être déficitaires, certains déficits vitaminiques pouvant être plus apparents que réels comme nous l'avons montré pour la riboflavine [29].…”
Section: Le Traitement Hospitalierunclassified